Response of Brachiaria brizantha cv. Piatã pastures to nitrogen fertilization (Research, Society and Development, 2020)
With the objective to evaluate the effects of nitrogen levels (0, 40, 80, 120 and 160 kg of N ha-1) on green dry matter (GDM) yield and morphogenetic and structural characteristics and nitrogen nutrition index (NNI) of Brachiaria brizantha cv. Piatã, was installed an experiment under field conditions in Roraima´s savannas. Nitrogen fertilization increased significantly (P